General survey on avifaunal composition of Betana wetland, Morang, Province number 1, Eastern Nepal - Kharel, Milan (BIBECHANA, 2018)
The present study conducted in Betana wetland, Morang, Province number 1, Nepal. The study based on the field survey in order to find out the avifaunal composition. In the present study, total 320 individuals of birds belonging 49 species, 30 families and 15 orders reported from Betana wetland based on field observation. The highest proportions of individuals recorded from the sampling station F1 forest area was 35% (n=112). The highest number of species (n= 15) recorded belong to the order Passeriformes with nine families, followed by Coraciformes with three families and four species then Pelicaniformes with two families and six species. Of them, two species viz. Grey-headed fish eagle (Icthyophaga humilis) and Lesser Adjutant Stork (Leptoptilos javanicus ) are kept under near threatened (NT) and vulnerable (VU) category of IUCN Red List of threatened species. About 70 % of total bird recorded was resident type and about 35% of total recorded bird species common in abundance. The species richness and abundance of avifauna found higher in winter season than summer. Compared to the previous study, birds belonging to four more families and five more orders recorded this time. The Shanonn–Weiner diversity index and species evenness of avifauna from the study area found 1.332 and 0.789 respectively. BIBECHANA 16 (2019) 154-164